Hydrogel dressing for post-fire needle healing and scar prevention and preparation method thereof
Patent Information
- Application Number
- CN202610145980.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-02
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-02-02
AI Technical Summary
首先,在时间维度上,大多数载药系统采用单一释放机制,无法匹配火针创面三阶段的动态需求:炎性期需要快速释放抗炎成分以遏制急性炎症,而现有制剂常出现初期“突释”后迅速枯竭,或缓释不足导致抗炎滞后;进入重塑期后又因药物储备耗尽而无法持续抑制纤维化,致使瘢痕风险上升
1、本发明的双网络结构的互穿设计适配创面边缘与中心的功能差异,中药成分形成区域化分布,边缘区促愈成分浓度高,加速再上皮化;中心区防瘢成分长效作用,抑制纤维化。临床应用中,创面边缘愈合速度提升30%,中心区瘢痕发生率降低40%,解决了均质化产品的区域适配难题。
Smart Images

Figure CN121944208B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of post-fire needling care technology, specifically relating to a hydrogel dressing for use on wounds after traditional Chinese medicine fire needling treatment, which has both healing-promoting and scar-preventing functions, and its preparation method. Background Technology
[0002] Post-fire needling care refers to the systematic intervention process for the micro-wounds formed on the skin after fire needling treatment. The aim is to promote wound healing, control inflammatory responses, prevent infection, and reduce scar formation. Due to the unique structural characteristics of fire needling wounds—deep heat damage in the central area and shallow heat diffusion in the peripheral area—the healing process exhibits a dual dynamic pattern of spatial partitioning (central and peripheral areas) and temporal stages (inflammatory, proliferative, and remodeling phases). Ideal post-operative care should precisely release drug components with corresponding functions according to the biological needs of different stages and areas, achieving orderly regulation of "anti-inflammatory—healing-preventing—scarring prevention." Therefore, nursing materials must not only possess good biocompatibility and physical stability but also have spatiotemporally controllable drug delivery capabilities to match the complex repair mechanisms of the wound.
[0003] Currently, commonly used post-fire needling care methods mainly include traditional dressings such as gauze, general-purpose hydrogels, and some topical Chinese medicine preparations. Gauze primarily prevents external contamination through physical covering, but it lacks moisturizing properties and pharmacological activity, easily adheres to the wound, and may cause secondary damage during replacement. While general-purpose hydrogels have some moisturizing and cooling effects, they also lack targeted drug release capabilities and cannot respond to the needs of different stages of the wound.
[0004] Existing technologies suffer from multiple shortcomings, severely limiting the effectiveness and safety of post-fire needling care. Firstly, in terms of time, most drug delivery systems employ a single release mechanism, failing to meet the dynamic needs of the three stages of the fire needling wound: during the inflammatory phase, rapid release of anti-inflammatory components is required to suppress acute inflammation, but existing formulations often experience an initial "burst release" followed by rapid depletion, or insufficient sustained release leading to delayed anti-inflammatory effects; during the remodeling phase, drug reserves are depleted, hindering sustained inhibition of fibrosis and increasing the risk of scarring. Secondly, regarding spatial control, traditional formulations cannot achieve differentiated drug delivery by region, such as concentrating anti-scarring components in the central area and promoting healing components in the peripheral area, resulting in resource misallocation due to cross-release of drugs. Furthermore, chemical permeation enhancers (such as azone and menthol) added to improve transdermal absorption efficiency are irritating to newly formed epithelial cells and may exacerbate tissue damage; while some antibacterial components (such as silver ions) can reduce the probability of infection, they exhibit cytotoxicity, interfering with the normal repair process. Structurally, most hydrogels are single-network systems, making it difficult to balance mechanical strength and flexibility, resulting in easy breakage or deformation and an inability to stably maintain a moist healing environment. Finally, traditional Chinese medicine formulas often rely on empirical compatibility, lacking scientific analysis of the synergistic mechanisms of multiple components. Crude extraction processes lead to low purity of active ingredients and high impurity content, easily inducing allergic reactions and limiting their application in precise wound management. Summary of the Invention
[0005] This invention, based on the spatiotemporal heterogeneity of healing patterns in fire needling wounds, constructs a "dual-network structure" hydrogel carrier. Through network synergy, it adapts to the functional differences between the wound edge and center, achieving regionalized drug distribution. Simultaneously, it screens active ingredients from traditional Chinese medicines with different release characteristics, forming a time-sequential release system of "rapid anti-inflammatory, stable healing promotion, and long-lasting scar prevention." Furthermore, this invention explores the multiple functions of traditional Chinese medicine components, replacing chemical penetration enhancers with natural ingredients to resolve the conflict between safety and function. At the same time, the synergy between the carrier structure and the drug system enhances the overall therapeutic effect.
[0006] This invention utilizes a dual-network structure formed by an ionic cross-linked network and a physically entangled network to adapt to the heterogeneity of wound regions, achieving regionalized adaptation of physical properties. The ionic cross-linked network provides skeletal strength, adapting to the mechanical stress environment of the wound center; the physically entangled network (PVP-CMC-Na) provides high water retention and viscoelasticity, adapting to the re-epithelialization requirements of the wound periphery. Simultaneously, the interpenetrating nature of the dual-network structure allows for regional distribution of the active ingredients of traditional Chinese medicine, with higher drug concentrations in the periphery than in the center, thus achieving spatial efficacy in promoting healing at the periphery and preventing scarring in the center.
[0007] This invention constructs a time-sequential synergistic release system based on the physicochemical properties and release behavior of Phellodendron amurense extract, Bletilla striata polysaccharide, and Centella asiatica total glycosides. Phellodendron amurense extract exhibits good water solubility, with a cumulative release of >60% within 12 hours during the inflammatory response phase, rapidly controlling inflammation. Bletilla striata polysaccharide, with its strong viscosity, is released steadily during the proliferation phase, continuously promoting epithelial cell migration. Centella asiatica total glycosides, with its strong hydrophobicity, provides long-lasting sustained release during the remodeling phase (cumulative release ≈85% within 72 hours), continuously inhibiting scar formation and achieving dynamic adaptation throughout the entire cycle of "inflammatory phase-proliferation phase-remodeling phase."
[0008] The inventors creatively discovered that Bletilla striata polysaccharide possesses a dual function of promoting healing and penetration. Its bioadhesive properties form a hydrophilic biofilm that not only prolongs drug retention time but also softens the skin barrier through hydration, enhancing transdermal drug delivery efficiency while ensuring biocompatibility. Furthermore, they found that Phellodendron amurense extract, Bletilla striata polysaccharide, and total glycosides of Centella asiatica collectively achieve anti-inflammatory, healing-promoting, and scar-preventing functions. The anti-inflammatory effect of Phellodendron amurense extract lays the foundation for healing promotion, the healing-promoting effect of Bletilla striata polysaccharide accelerates wound closure, and the scar-preventing effect of total glycosides of Centella asiatica optimizes tissue remodeling; the synergistic effect of these three components achieves the desired therapeutic effect.
[0009] The hydrogel dressing of the present invention consists of three parts: a dual-network structure substrate, active ingredients of traditional Chinese medicine, and auxiliary ingredients. The selection of each component is based on the healing requirements and synergistic mechanism of fire needling wounds, as detailed below: (I) Design and selection of dual-network structure substrate The dual-network structure consists of an ionic cross-linked network and a physically entangled network, which achieve a synergistic enhancement effect through interpenetration / semi-interpenetration. The selection criteria and specifications of each component are as follows: 1. Ionic cross-linked network Sodium alginate is a natural anionic polysaccharide extracted from brown algae, exhibiting excellent biocompatibility, biodegradability, and ionic responsiveness. The carboxyl groups on the sodium alginate molecular chain form a cross-linked structure with Ca²⁺, enabling rapid hydrogel molding and improving preparation efficiency. The cross-linked network possesses excellent skeletal strength, supporting the overall shape of the dressing, resisting mechanical stress in the wound center, and preventing deformation and breakage. As a natural polysaccharide, sodium alginate has good biocompatibility, is non-irritating, and possesses a certain degree of liquid absorption capacity, capable of absorbing inflammatory exudate in the wound center.
[0010] Sodium alginate with a molecular weight of 100-200 kDa and a viscosity of 200-400 mPa·s (1% aqueous solution, 25℃) is selected. This specification can ensure sufficient ionic cross-linking reaction and avoid dissolution difficulties or abnormal viscosity caused by large molecular weight.
[0011] As a raw material, sodium alginate is used at a weight ratio of 2.0 parts (in the raw materials). If the amount is less than 2.0 parts, the ionic cross-linking network will not be formed sufficiently and the skeleton strength will be insufficient; if the amount is more than 2.0 parts, the hydrogel will become more brittle and less flexible, affecting the wound adhesion.
[0012] 2. Physically entangled networks A physical entanglement network is formed by combining polyvinylpyrrolidone (PVPK90) and sodium carboxymethyl cellulose (CMC-Na).
[0013] PVPK90 exhibits excellent water solubility, biocompatibility, and film-forming properties. The pyrrolidone groups on its molecular chain can form hydrogen bonds with CMC-Na, enhancing network stability. CMC-Na, with its good water solubility and high viscosity, has carboxyl and hydroxyl groups on its molecular chain that further strengthen hydrogen bonding. Simultaneously, its own molecular chain entanglement enhances the network's viscoelasticity. The compound system possesses ultra-high water retention, locking in a large amount of moisture to provide a stable, moist environment for re-epithelialization at the wound edge, while also compensating for the brittleness of ionic cross-linked networks, giving the dressing both strength and elasticity.
[0014] For the raw material, PVP of type K90 with a molecular weight of 1000-1500 kDa and a moderate chain length is selected, which provides the best entanglement effect with CMC-Na. For CMC-Na, a product with a degree of substitution of 0.7-0.9 is selected. Too high a degree of substitution will result in abnormal viscosity, while too low a degree of substitution will result in insufficient water retention.
[0015] As raw materials, CMC-Na is 1.5 parts and PVPK90 is 4.0 parts. If CMC-Na is less than 1.5 parts, the water retention and viscoelasticity will be insufficient, and if it is more than 1.5 parts, the viscosity will be too high, which will hinder drug release. If PVPK90 is less than 4.0 parts, the entanglement effect will be poor, and if it is more than 4.0 parts, the strength will decrease, which will affect the stability of the dressing.
[0016] 3. Dual-network collaborative mechanism An ionic cross-linked network (sodium alginate-Ca²⁺) acts as a "rigid skeleton," providing structural strength and liquid absorption capacity, while a physically entangled network (PVP-CMC-Na) acts as a "flexible filler," providing water retention and flexibility. The two are combined through a process of blending followed by unified ionic cross-linking to form an interpenetrating / semi-interpenetrating structure, resulting in a synergistic reinforcing effect. Compared to a single ionic cross-linked network, water retention is improved by over 30%, and elastic recovery rate is improved by 50%; compared to a single physically entangled network, compressive modulus is improved by 150%, and liquid absorption and water-locking capacity is improved by 20%, comprehensively optimizing the physical properties of the dressing.
[0017] (II) Design and Selection of Self-Penetration-Promoting Synergistic System of Traditional Chinese Medicine The active ingredients of this traditional Chinese medicine consist of Phellodendron bark extract, Bletilla striata polysaccharide, and total glycosides of Centella asiatica. Through a specific ratio, they form a synergistic system of "anti-inflammatory-healing-scar prevention," while Bletilla striata polysaccharide replaces chemical penetration enhancers to achieve self-penetration enhancement, as detailed below: 1. Phellodendron bark extract The content of berberine hydrochloride (Ber) in the extract of Phellodendron amurense is ≥50% (determined by HPLC). The extraction method of Phellodendron amurense extract is as follows: Phellodendron amurense herb is pulverized and passed through a 40-mesh sieve, 10 times the amount of 70% ethanol is added, and the mixture is refluxed and extracted twice (2 hours each time). The extracts are combined and concentrated under reduced pressure to a relative density of 1.20-1.25 (60℃), and then spray-dried to obtain the extract.
[0018] Phellodendron bark extract, as a core anti-inflammatory component during the inflammatory response phase, targets the pathogenesis of "heat toxin accumulation" during fire needling. It inhibits the activation of the NF-κB inflammatory pathway, reduces the secretion of inflammatory factors such as TNF-α, IL-6, and IL-1β, and also has a certain antibacterial effect, preventing wound infection.
[0019] As a raw material, the dosage of Phellodendron bark extract is 5-7 parts. If it is less than 5 parts, the anti-inflammatory effect will be insufficient and it will be unable to control the initial inflammation; if it is more than 7 parts, it may be toxic to newly formed epithelial cells and affect healing.
[0020] 2. Bletilla striata polysaccharides The purity of Bletilla striata polysaccharide is ≥85% (determined by phenol-sulfuric acid method), and the molecular weight is 50-100 kDa (determined by gel permeation chromatography). The extraction steps of Bletilla striata polysaccharide are as follows: Bletilla striata medicinal material is pulverized and passed through a 60-mesh sieve, 20 times the amount of deionized water is added, and the mixture is refluxed at 80℃ for 3 times (3 hours each time). The extracts are combined and concentrated under reduced pressure to 1 / 10 of the original volume. 3 times the amount of 95% ethanol is added and allowed to stand for 24 hours. The precipitate is collected by centrifugation and freeze-dried to obtain Bletilla striata polysaccharide.
[0021] Bletilla striata polysaccharide, as a healing-promoting component in the hydrogel dressing provided by this invention, can promote the migration and proliferation of epithelial cells, accelerate the epithelialization of the wound, and at the same time astringe and stop bleeding, reducing wound exudation; ② Permeation-promoting effect: forming a hydrophilic bioadhesive membrane, prolonging the drug residence time, softening keratin / necrotic tissue through hydration, reducing skin barrier resistance, promoting the transdermal absorption of Phellodendron amurense extract and Centella asiatica total glycosides, and replacing chemical permeation enhancers.
[0022] As a raw material, the amount of Bletilla striata polysaccharide used is 3-5 parts. If it is less than 3 parts, the healing and penetration-promoting effects will be insufficient; if it is more than 5 parts, the hydrogel viscosity will be abnormal, which will hinder the release of drugs and make it easy to tear off the new tissue when it is replaced.
[0023] 3. Total glycosides from Centella asiatica The total glycoside content of Centella asiatica is ≥80% (determined by HPLC). The extraction process of Centella asiatica total glycosides is as follows: Centella asiatica herb is pulverized and passed through a 40-mesh sieve, 15 times the amount of 75% ethanol is added, and the mixture is refluxed and extracted twice (1.5 h each time). The extracts are combined and concentrated under reduced pressure until no alcohol odor is detected. The mixture is extracted three times with ethyl acetate, and the organic phases are combined and concentrated under reduced pressure to dryness to obtain the total glycosides.
[0024] Total glycosides of Centella asiatica, as the core anti-scarring component in the hydrogel dressing provided by this invention, can regulate fibroblast proliferation and differentiation, inhibit excessive synthesis of type I collagen, promote the expression of type III collagen, optimize collagen arrangement, and reduce scar formation.
[0025] As a raw material, the dosage of total glycosides of Centella asiatica is 2-3 parts. If it is less than 2 parts, the scar prevention effect will be insufficient; if it is more than 3 parts, it will inhibit the normal proliferation of fibroblasts and delay the formation of granulation tissue.
[0026] 4. Synergistic mechanism of traditional Chinese medicine formulation The hydrogel dressing provided by this invention contains the following herbal ingredients in the following proportions: 5-7 parts Phellodendron bark extract, 3-5 parts Bletilla striata polysaccharide, and 2-3 parts Centella asiatica total glycosides. The viscosity and penetration-enhancing ability of Bletilla striata polysaccharide are optimally balanced, efficiently carrying the components of Phellodendron bark and Centella asiatica for penetration without hindering release. The ratio of Phellodendron bark to Centella asiatica ensures a seamless transition from early anti-inflammatory to late-stage scar prevention. Phellodendron bark rapidly controls inflammation, laying the foundation for healing and scar prevention, while Centella asiatica provides long-lasting, sustained release that precisely regulates collagen synthesis during the remodeling period. Through the synergistic effect of these three ingredients, the anti-inflammatory effect is increased by 25%, the healing speed by 30%, and the scar prevention effect by 40%, significantly superior to any single component.
[0027] (iii) Auxiliary ingredients The hydrogel dressing provided by this invention also contains auxiliary ingredients glycerin, ethylparaben, and water. Glycerin, as a moisturizer, is used at 10.0 parts to enhance the water retention capacity of the hydrogel, prevent it from drying and hardening, and improve skin adhesion comfort. Ethylparaben, as a preservative, is used at 0.1 parts, meeting medical standards, inhibiting microbial growth, extending shelf life, and is non-irritating. Deionized water, as a solvent, is used to bring the total amount to 100 parts to ensure that all components are fully dissolved and dispersed, maintaining the homogeneity of the hydrogel.
[0028] III. Preparation Method of Hydrogel Dressing The method for preparing hydrogel dressings provided by this invention involves first pre-dispersing the active ingredients of traditional Chinese medicine in a Bletilla striata polysaccharide solution, utilizing its viscosity to achieve uniform encapsulation and avoid subsequent mixing and agglomeration; stepwise dissolution of the polymer matrix to ensure uniform dispersion of the dual-network precursor; light-protected operation, gradient stirring, and vacuum degassing to ensure the activity of the traditional Chinese medicine ingredients and the uniformity of the hydrogel structure; and gentle ionic crosslinking and irradiation sterilization to avoid extreme conditions from damaging product performance. Through four core processes, the dual-network structure is constructed and the traditional Chinese medicine ingredients are uniformly loaded. The process parameters have been repeatedly optimized to ensure stable product quality, making it suitable for large-scale industrial production. The specific steps are as follows:
[0029] S1: Disperse the prescribed amount of Bletilla striata polysaccharide in 15 parts of deionized water preheated to 50-60℃, stir at 300r / min for 10 minutes, then increase to 800r / min and stir for 20 minutes to form a homogeneous viscous gel; add Phellodendron amurense extract and Centella asiatica total glycosides in sequence, stir at 800r / min for 10 minutes and at 1000r / min for 15 minutes respectively, and cool naturally to 25±2℃ to obtain the pre-dispersion of active ingredients.
[0030] S2: Dissolve sodium alginate, CMC-Na, and PVPK90 in 65 parts of room temperature deionized water in sequence, and stir at 500 r / min for 15 minutes, 600 r / min for 10 minutes, and 800 r / min for 30 minutes respectively to form a homogeneous and transparent substrate solution.
[0031] Specifically, 65 parts of deionized water (room temperature 25±2℃); first add sodium alginate, stir at 500 r / min for 15 min, then add CMC-Na, stir at 600 r / min for 10 min, and finally add PVPK90, stir at 800 r / min for 30 min; the solution is uniform and transparent, with no visible particles.
[0032] S3. Thoroughly mix the pre-dispersed active ingredient solution with the substrate solution, add auxiliary ingredients, remove air bubbles, and obtain a pre-gelled blend.
[0033] Specifically, under light-protected conditions, the pre-dispersion of the active ingredient was slowly injected into the substrate solution at a rate of 5 mL / min, and stirred at a low speed of 500 r / min for 30 minutes; glycerol and ethylparaben were added, and the mixture was stirred at 800 r / min for 15 minutes; the stirring speed was increased to 1500 r / min and homogenized for 20 minutes, followed by degassing under a vacuum of -0.08 MPa for 30 minutes to obtain a pre-gelled blend. S4: Inject the pregelated blend into a sterile mold, spray with 5% (w / v) calcium chloride solution using a spray method, spray pressure 0.25-0.3MPa, spray volume 4.5-5mL / 100cm², crosslink at room temperature for 10-20 minutes; rinse 3 times with sterile deionized water, 5 minutes each time, flow rate 10mL / min; cut into the required specifications under sterile conditions, seal in aluminum foil bags, and sterilize by 25kGy dose cobalt-60 irradiation to obtain the finished product.
[0034] Specifically, the mold is a sterile polytetrafluoroethylene flat plate mold (20cm×20cm×0.5cm); cross-linking method: spray method, 5% (w / v) calcium chloride solution, spray pressure 0.3MPa, spray volume 5mL / 100cm²; cross-linking time: 15min (room temperature 25±2℃); rinsing: rinse 3 times with sterile deionized water (5min each time, flow rate 10mL / min); cutting: cut to 5cm×5cm specifications under sterile conditions; packaging: sealed in aluminum foil composite bags; sterilization: cobalt-60 irradiation, dose 25kGy.
[0035] This invention achieves a breakthrough in fire needle wound care technology through the dual innovation of a dual-network structure carrier and a self-penetrating traditional Chinese medicine synergistic system, and has the following significant beneficial effects compared with existing technologies: 1. The interpenetrating design of the dual-network structure of this invention adapts to the functional differences between the wound edge and center, resulting in a regional distribution of the herbal ingredients. The edge area has a high concentration of healing-promoting ingredients, accelerating re-epithelialization; the central area has a long-lasting anti-scarring effect, inhibiting fibrosis. In clinical applications, the wound edge healing speed is increased by 30%, and the incidence of scarring in the central area is reduced by 40%, solving the regional adaptation problem of homogenized products.
[0036] 2. The time-release characteristics of the Chinese herbal ingredients in this hydrogel dressing perfectly match the three-stage healing pattern of fire needle wounds. Phellodendron bark extract has a rapid anti-inflammatory effect (cumulative release >60% in 12 hours), Bletilla striata polysaccharide promotes stable healing, and Centella asiatica total glycosides have a long-lasting anti-scarring effect (cumulative release ≈85% in 72 hours), achieving seamless treatment from the "inflammatory phase to the proliferation phase to the remodeling phase" and avoiding the drawbacks of a single release mode.
[0037] 3. The dual function of Bletilla striata polysaccharide in promoting healing and penetration completely replaces chemical penetration enhancers such as azone, increasing drug transdermal efficiency by 30-40% while avoiding the irritating damage caused by chemical penetration enhancers. The dressing has been verified by cytotoxicity experiments, showing a cell survival rate >95%, with no risk of allergies, making it suitable for the elderly, diabetic patients, and other individuals with weakened repair capabilities.
[0038] 4. The dual-network structure of this hydrogel dressing enables it to have long-lasting water retention (48h water retention rate ≥85%), excellent mechanical properties (compression modulus ≈25kPa, elastic recovery rate >90%), strong liquid absorption and water retention capacity (water absorption ratio ≈8 times, centrifugal water retention rate >80%), and microenvironment stability (pH stable at 7.0±0.3), far exceeding that of single-network or simple blended hydrogels, providing an ideal moist healing environment for wounds.
[0039] 5. This invention uses a specific ratio of three Chinese herbal ingredients to form a synergistic system of anti-inflammatory, healing-promoting and scar-preventing effects. Compared with single-drug groups, the anti-inflammatory effect is improved by 25%, the healing speed is improved by 30%, and the scar-preventing effect is improved by 40%. It can also regulate collagen arrangement, making the new skin closer to normal tissue, thus solving the problem of single function of traditional Chinese herbal preparations.
[0040] 6. The preparation process of the hydrogel dressing provided by this invention is mild, requires no extreme equipment, has clear and easy-to-control steps, allows for precise adjustment of key parameters, and ensures good consistency between product batches. The mold can be flexibly adjusted in size to adapt to the needs of wounds in different locations, making it suitable for large-scale industrial production. Attached Figure Description
[0041] Figure 1 A cross-section (left) and a magnified view (right) of the hydrogel dressing under a scanning electron microscope provided for the embodiment.
[0042] Figure 2 Statistical charts of gel moisture retention rate and compression modulus after 48 hours for experimental groups 1-5, control groups 1-3 and control group 7 respectively.
[0043] Figure 3 The comparison charts show the gel absorption and shrinkage capacity of experimental groups 1-5, control groups 1-3, and control group 7, as well as the comparison charts show the pH fluctuation range over 24 hours.
[0044] Figure 4 The graph shows the comparison of gel elastic recovery rates for experimental groups 1-5, control groups 1-3, and control group 7.
[0045] Figure 5 The cumulative release rate of berberine hydrochloride in the gel is shown for experimental groups 1-5, control group 4 and control group 8, respectively, as well as the cumulative release rate of asiaticoside in the gel is shown for experimental groups 1-5, control group 6 and control group 8, respectively.
[0046] Figure 6 Statistical charts showing the transdermal efficiency of berberine hydrochloride and asiaticoside in gels provided for experimental groups 1-5, control group 4, control group 6, and control group 88, respectively.
[0047] Figure 7The statistical comparison charts of the anti-inflammatory effects of the gels provided for experimental groups 1-5 and control groups 4-8 are shown.
[0048] Figure 8 The statistical comparison charts of the gel healing effects provided for experimental groups 1-5 and control groups 4-8 are shown.
[0049] Figure 9 The statistical comparison charts of the anti-scarring effects of the gel provided for experimental groups 1-5 and control groups 4-8 are shown. Detailed Implementation
[0050] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application. Reagents not described in detail herein are all conventional reagents and are commercially available.
[0051] The following embodiments are used to verify the feasibility and superiority of the technical solution of the present invention. The amount of raw materials and process parameters in each embodiment are adjusted within the optimization range, and the technical effects of the present invention can be achieved.
[0052] Experimental group 1 Raw materials (parts by weight): Sodium alginate 2.0 parts, CMC-Na 1.5 parts, PVPK90 4.0 parts, Phellodendron bark extract (berberine content 50%) 6.0 parts, Bletilla striata polysaccharide (purity 85%) 4.0 parts, Centella asiatica total glycosides (glycoside content 80%) 2.5 parts, glycerin 10.0 parts, ethylparaben 0.1 parts, deionized water to 100 parts.
[0053] Preparation steps: S1: Disperse 4.0 parts of Bletilla striata polysaccharide in 15 parts of 60℃ deionized water, stir at 300r / min for 10min, and stir at 800r / min for 20min to form a gel; add 6.0 parts of Phellodendron chinense extract, stir at 800r / min for 10min; add 2.5 parts of Centella asiatica total glycosides, homogenize and stir at 1000r / min for 15min, and cool to 25℃ to obtain a pre-dispersion.
[0054] S2: Dissolve 2.0 parts of sodium alginate in 65 parts of deionized water and stir at 500 r / min for 15 min; add 1.5 parts of CMC-Na and stir at 600 r / min for 10 min; add 4.0 parts of PVPK90 and stir at 800 r / min for 30 min to obtain a homogeneous and transparent substrate solution.
[0055] S3: Under light-protected conditions, the pre-dispersion was injected into the substrate solution at a rate of 5 mL / min and stirred at 500 r / min for 30 min; 10.0 parts of glycerol and 0.1 parts of preservative were added and stirred at 800 r / min for 15 min; homogenized and stirred at 1500 r / min for 20 min; and degassed under vacuum at -0.08 MPa for 30 min to obtain the pre-gelled blend.
[0056] S4: Pre-gelled material is injected into a mold, sprayed with 5% calcium chloride solution (0.3MPa, 5mL / 100cm²), cross-linked for 15min; rinsed 3 times with sterile deionized water, cut into 5cm×5cm specifications, sealed in aluminum foil bags, and sterilized by 25kGy cobalt-60 irradiation to obtain the finished product.
[0057] Experimental group 2 Ingredients (parts by weight): Sodium alginate 2.0 parts, CMC-Na 1.5 parts, PVPK90 4.0 parts, Phellodendron bark extract 5.0 parts, Bletilla striata polysaccharide 3.0 parts, Centella asiatica total glycosides 2.0 parts, glycerin 10.0 parts, ethylparaben 0.1 parts, deionized water to 100 parts.
[0058] Preparation steps: Same as Experimental Group 1, only the dosage of active ingredients of traditional Chinese medicine was adjusted, and the other process parameters remained unchanged. The anti-inflammatory inhibition rate of this embodiment is about 50%, the healing promotion rate is about 65%, and the scar prevention inhibition rate is about 40%, all of which meet the needs of fire needling wound care and are a low-cost adaptation solution.
[0059] Experimental group 3 Ingredients (parts by weight): Sodium alginate 2.0 parts, CMC-Na 1.5 parts, PVPK90 4.0 parts, Phellodendron bark extract 7.0 parts, Bletilla striata polysaccharide 5.0 parts, Centella asiatica total glycosides 3.0 parts, glycerin 10.0 parts, ethylparaben 0.1 parts, deionized water to 100 parts.
[0060] Preparation steps: Same as Experimental Group 1, only the dosage of the active ingredients of traditional Chinese medicine was adjusted, and the other process parameters remained unchanged. The anti-inflammatory inhibition rate of this embodiment is about 60%, the healing promotion rate is about 72%, and the scar prevention inhibition rate is about 48%, making it suitable for fire needle wounds with severe inflammatory reactions.
[0061] Experimental group 4 Ingredients (parts by weight): Sodium alginate 1.8 parts, CMC-Na 1.2 parts, PVPK90 3.5 parts, Phellodendron bark extract 6.0 parts, Bletilla striata polysaccharide 4.0 parts, Centella asiatica total glycosides 2.5 parts, glycerin 10.0 parts, ethylparaben 0.1 parts, deionized water to 100 parts.
[0062] Preparation steps: Same as Experimental Group 1, only the amount of polymer substrate was adjusted, and the other process parameters remained unchanged. The water retention rate of this embodiment was approximately 83% after 48 hours, the compression modulus was approximately 22 kPa, and the elastic recovery rate was approximately 88%. The physical properties were slightly lower than those of Experimental Group 1, but still met the usage requirements, making it a lightweight adaptation solution.
[0063] Experimental group 5 Raw materials (parts by weight): Same as experimental group 1.
[0064] Preparation steps: Except for the crosslinking parameters, the remaining steps were the same as in Experimental Group 1. The crosslinking parameters were adjusted as follows: 5% calcium chloride solution, spray pressure 0.25 MPa, spray volume 4.5 mL / 100 cm², and crosslinking time 20 min. This example showed a water retention rate of approximately 82% after 48 h, a compression modulus of ≈23 kPa, and an elastic recovery rate of ≈89%, demonstrating stable performance and suitability for various production equipment.
[0065] The following control groups were used to compare and verify the technical advantages of the present invention. Each control group lacked the core innovative points of the present invention (dual network structure, synergistic system of traditional Chinese medicine, self-penetration-promoting function, etc.), as detailed below: Control group 1: Single ion-crosslinked network hydrogel Ingredients (parts by weight): Sodium alginate 2.0 parts, Phellodendron bark extract 6.0 parts, Bletilla striata polysaccharide 4.0 parts, Centella asiatica total glycosides 2.5 parts, Glycerin 10.0 parts, Ethylparaben 0.1 parts, Deionized water to 100 parts.
[0066] Preparation steps: Remove CMC-Na and PVP, use only sodium alginate as the substrate, and crosslink and mold according to the steps of experimental group 1, while keeping other process parameters unchanged.
[0067] The single ion-crosslinked network hydrogel obtained in control group 1 had a water retention rate of ≤60% after 48 hours, making it unable to maintain a long-term moist environment. Its elastic recovery rate was only 60%, indicating it was prone to breakage. Its liquid absorption and water retention capacity was weak (water absorption ratio ≈4 times), failing to meet the needs of inflammatory exudation.
[0068] Control group 2: Single physically entangled network hydrogel Raw materials (parts by weight): CMC-Na 1.5 parts, PVPK90 4.0 parts, Phellodendron bark extract 6.0 parts, Bletilla striata polysaccharide 4.0 parts, Centella asiatica total glycosides 2.5 parts, glycerin 10.0 parts, ethylparaben 0.1 parts, deionized water to 100 parts.
[0069] Preparation steps: Sodium alginate is removed, calcium ion crosslinking is not performed, and the gel is formed by physical entanglement according to the steps of experimental group 1, while the other process parameters remain unchanged.
[0070] The single physically entangled network hydrogel obtained in control group 2 has a compression modulus of ≈10kPa and is easily deformed; the water retention rate by centrifugation is ≈70%, and it is easy to collapse after liquid absorption; the structural stability is poor and it is easy to harden after long-term storage.
[0071] Control group 3: Simple blended hydrogel Ingredients (parts by weight): Sodium alginate 2.0 parts, CMC-Na 1.5 parts, PVPK90 4.0 parts, Phellodendron bark extract 6.0 parts, Bletilla striata polysaccharide 4.0 parts, Centella asiatica total glycosides 2.5 parts, glycerin 10.0 parts, ethylparaben 0.1 parts, deionized water to 100 parts.
[0072] Preparation steps: No calcium ion crosslinking is performed; the mixture is simply mixed evenly to form a gel naturally. All other process parameters remain the same as in experimental group 1.
[0073] The simple blended hydrogel provided in control group 3 had no synergistic enhancement effect, and its water retention rate and mechanical properties were between those of a single network; its structure was heterogeneous, it was easy to stratify, and its drug release fluctuated greatly; its microenvironment stability was poor (pH fluctuation > 0.8).
[0074] Control group 4: Dual-network hydrogel containing only Phellodendron amurense extract Ingredients (parts by weight): Sodium alginate 2.0 parts, CMC-Na 1.5 parts, PVPK90 4.0 parts, Phellodendron bark extract 6.0 parts, Glycerin 10.0 parts, Ethylparaben 0.1 parts, Deionized water to 100 parts.
[0075] Preparation steps: Remove Bletilla striata polysaccharide and Centella asiatica total glycosides, and the remaining process parameters are the same as those in experimental group 1.
[0076] The dual-network hydrogel containing only Phellodendron amurense extract provided in control group 4 had no healing-promoting or scar-preventing effects, only anti-inflammatory effects; low drug transdermal efficiency (decreased by 30%); slow healing speed; and high risk of scarring.
[0077] Control group 5: Double-network hydrogel containing only Bletilla striata polysaccharide Raw materials (parts by weight): Sodium alginate 2.0 parts, CMC-Na 1.5 parts, PVPK90 4.0 parts, Bletilla striata polysaccharide 4.0 parts, glycerin 10.0 parts, ethylparaben 0.1 parts, deionized water to 100 parts.
[0078] Preparation steps: Remove the extract of Phellodendron bark and total glycosides of Centella asiatica, and keep the other process parameters the same as those in experimental group 1.
[0079] The double-network hydrogel provided in control group 5, which only contains Bletilla striata polysaccharide, has insufficient anti-inflammatory properties, resulting in prolonged inflammation; it has no anti-scarring effect, a high incidence of scarring, and poor healing quality.
[0080] Control group 6: Dual-network hydrogel containing only total asiaticosides Raw materials (parts by weight): 2.0 parts sodium alginate, 1.5 parts CMC-Na, 4.0 parts PVPK90, 2.5 parts total glycosides of Centella asiatica, 10.0 parts glycerol, 0.1 parts ethylparaben, and deionized water to 100 parts.
[0081] Preparation steps: Remove the extract of Phellodendron bark and the polysaccharide of Bletilla striata, and keep the other process parameters the same as those in experimental group 1.
[0082] The control group 6 provided a dual-network hydrogel containing only total asiaticosides, which had no anti-inflammatory or healing-promoting effects, delayed healing, low transdermal drug efficiency (decreased by 40%), and limited scar prevention effect.
[0083] Control group 7: Blank matrix dual-network hydrogel Raw materials (parts by weight): 2.0 parts sodium alginate, 1.5 parts CMC-Na, 4.0 parts PVPK90, 10.0 parts glycerin, 0.1 parts ethylparaben, and deionized water to 100 parts.
[0084] Preparation steps: Remove all Chinese herbal ingredients, and keep the remaining process parameters the same as those in experimental group 1.
[0085] The control group 7 provided blank matrix dual-network hydrogels that only had physical performance advantages, but no pharmacological activity, and the healing quality and scar incidence were not ideal.
[0086] Control group 8: Herbal hydrogel with added chemical penetration enhancers Ingredients (parts by weight): Sodium alginate 2.0 parts, CMC-Na 1.5 parts, PVPK90 4.0 parts, Phellodendron bark extract 6.0 parts, Bletilla striata polysaccharide 4.0 parts, Centella asiatica total glycosides 2.5 parts, azone 1.0 part, glycerin 10.0 parts, ethylparaben 0.1 parts, deionized water to 100 parts.
[0087] Preparation steps: Azone was added during the S3 blending stage, and the remaining process parameters were the same as those in experimental group 1.
[0088] The herbal hydrogel provided in control group 8 with added chemical penetration enhancers had poor biocompatibility, and azone irritated newly formed wounds; excessive drug penetration posed a risk of systemic adverse reactions; long-term use damaged the skin barrier.
[0089] The following validation examples comprehensively validated the hydrogels prepared in experimental groups 1-5 and control groups 1-8 through in vitro performance testing, drug release testing, and cell pharmacological activity testing. All tests followed the "Medical Hydrogel Dressings" (YY / T0962-2014) and related pharmacological experimental standards. Three parallel samples were set up for each group of samples, and the results were taken as mean ± standard deviation.
[0090] Verification Example 1: Comprehensive Verification of the Physical Performance of a Dual-Network Structure Test samples: gels provided by experimental groups 1-5, control groups 1-3 (single network / simple blend system), and control group 7 (blank matrix).
[0091] Water retention test: The sample was cut into 5cm×5cm×0.5cm, weighed (W0), and placed in a constant temperature and humidity chamber at 37℃ and 50%RH. The samples were weighed (Wt) at 6h, 12h, 24h, and 48h respectively. The water retention rate was calculated as (Wt / W0)×100%.
[0092] Mechanical property testing: The compression modulus was determined using a texture analyzer (compression rate 1 mm / min, compression ratio 30%); after compression, the elastic recovery rate was calculated as (recovered thickness / original thickness) × 100% after standing for 30 min.
[0093] Liquid absorption and water retention test: After the sample is lyophilized, it is weighed (Wd) and immersed in simulated exudate (PBS + 5% bovine serum albumin) for 24 hours. The weight is then measured (Ws). The water absorption ratio is calculated as (Ws-Wd) / Wd. Subsequently, the sample is centrifuged at 1000g for 10 minutes and weighed (Wc). The centrifugal water retention rate is calculated as (Wc-Wd) / (Ws-Wd)×100%.
[0094] Microenvironment stability test: The sample was covered with a simulated wound (collagen gel + HaCaT cells), and the pH value of the interface was monitored at 0h, 6h, 12h, and 24h using a pH meter.
[0095] According to such Figures 2-4 It can be seen that the physical properties of the hydrogels in experimental groups 1-5 are all superior to those in control groups 1-3, with experimental group 1 (optimal ratio) showing the best performance. Although experimental groups 4-5 are slightly lower than experimental group 1 in some indicators, they still meet the requirements for fire needle wound care. The single ionic network gel in control group 1 is brittle and has poor water retention. The single physical network gel in control group 2 has insufficient strength. The simple blended gel in control group 3 has no synergistic enhancement effect and cannot simultaneously achieve good water retention, mechanical properties, and microenvironment stability. Control group 7 is merely a blank matrix material, with physical properties similar to those in the examples, but without pharmacological activity.
[0096] Validation Example 2: Drug Release and Transdermal Permeation Validation Test samples: gels provided by experimental groups 1-5, control groups 4-6 (single-drug system), and control group 8 (chemical penetration enhancer).
[0097] In vitro drug release: A Franz diffusion cell (membrane-free) was used at 37℃ and 50 r / min. Samples were taken at 1h, 6h, 12h, 24h, 48h, and 72h, respectively. The concentrations of berberine hydrochloride (detection wavelength 265nm) and asiaticoside (detection wavelength 205nm) were determined by HPLC, and the cumulative release rate was calculated.
[0098] Transdermal permeation test: A porcine skin in vitro transdermal model (subcutaneous fat removed, thickness 0.5 mm) was used. After 24 h at 37℃ and 50 r / min, the skin tissue was peeled off, the drug was extracted with methanol, and the content was determined by HPLC. The transdermal efficiency was calculated as (total drug in the skin / total drug in the sample) × 100%. At the same time, HE-stained sections of the skin tissue were observed to assess irritation.
[0099] like Figure 5 and Figure 6 As shown, experimental groups 1-5 achieved the time-series release characteristics of "rapid release" of berberine hydrochloride and "long-acting sustained release" of asiaticoside, with significantly higher transdermal efficiency than control groups 4-6; although control group 8 had slightly higher transdermal efficiency, it was irritating to the skin; experimental groups 1-5 had no irritation and better biosafety.
[0100] Verification Example 3: Validation of anti-inflammatory, healing-promoting, and scar-preventing pharmacological activities Test samples: gels provided by experimental groups 1-5 and control groups 4-8, with PBS buffer as a blank control.
[0101] Anti-inflammatory experiment: LPS stimulation of RAW264.7 macrophages (1×10⁻⁶ cells) 6 Add sample extract (10% v / v) to the control group (cells / mL). After 24 hours, measure the secretion of TNF-α and IL-6 by ELISA and calculate the inhibition rate as (secretion of control group - secretion of experimental group) / secretion of control group × 100%.
[0102] Healing promotion experiment: HaCaT cell scratch assay (seeding density 5×10⁶) 5 (cells / mL), add sample extract (10% v / v), and observe the scratch healing rate under a microscope after 24 hours = (initial scratch width - 24h scratch width) / initial scratch width × 100%.
[0103] Scar prevention experiment: HSF cell culture (seeding density 2×10⁶) 5 Add sample extract (10% v / v) to cells / mL, and after 24 h, qPCR is used to measure the expression of COL1 and COL3 mRNA (internal reference gene GAPDH), and Western blot is used to measure the expression of α-SMA protein (internal reference protein Actin). The COL1 inhibition rate and the COL3 / COL1 ratio are calculated.
[0104] like Figures 7-9It can be seen that experimental groups 1-5 all showed significant synergistic effects in anti-inflammation, healing promotion, and scar prevention, with experimental group 1 (optimal ratio) showing the best effect; experimental group 3, due to the higher dosage of Phellodendron amurense extract, had a slightly better anti-inflammatory effect than other examples; control groups 4-6 only had certain effects on a single efficacy, and their overall effect was far inferior to the examples; control group 8, although its pharmacological activity was similar to the examples, had skin irritation; experimental groups 1-5 were non-irritating and had excellent overall efficacy, fully meeting the full-cycle nursing needs of fire needle wounds.
[0105] The above description is merely a preferred embodiment of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application.
Claims
1. A method for preparing a hydrogel dressing for promoting healing and preventing scarring after fire needling, characterized in that, Includes the following steps: (1) Disperse 3-5 parts of Bletilla striata polysaccharide in 15 parts of deionized water preheated to 50-60℃, stir at 300r / min for 10 minutes, then increase the stirring speed to 800r / min and stir for 20 minutes to form a uniform and viscous gel; add 5-7 parts of Phellodendron chinense extract and 2-3 parts of Centella asiatica total glycosides in sequence, stir at 800r / min for 10 minutes and at 1000r / min for 15 minutes respectively, and cool naturally to 25±2℃ to obtain the active ingredient pre-dispersion solution. Store in the dark and control the temperature not to exceed 60℃ to prevent the degradation of Centella asiatica total glycosides. (2) Dissolve 1.8~2.0 parts of sodium alginate, 1.2~1.5 parts of sodium carboxymethyl cellulose, and 3.5~4.0 parts of PVPK90 in 65 parts of room temperature deionized water, and stir at 500 r / min for 15 minutes, 600 r / min for 10 minutes, and 800 r / min for 30 minutes respectively to form a uniform and transparent substrate solution; (3) In a light-protected environment, the pre-dispersion of active ingredients is slowly injected into the substrate solution at a rate of 5 mL / min, and stirred at a low speed of 500 r / min for 30 minutes. Add 10 parts of glycerol and 0.1 parts of ethylparaben, and stir at 800 r / min for 15 minutes; increase the stirring speed to 1500 r / min and homogenize for 20 minutes, then degas under a vacuum of -0.08 MPa for 30 minutes to obtain a pregelated blend. (4) Inject the pregelated blend into a sterile mold, spray 5% calcium chloride solution using a spray method, spray pressure is 0.25-0.3MPa, spray volume is 4.5-5mL / 100cm², crosslink at room temperature for 10-20 minutes; rinse 3 times with sterile deionized water, each rinse time is 5 minutes, flow rate is 10mL / min; cut into the required specifications under sterile conditions, seal in aluminum foil bags, and sterilize by irradiation with 25kGy dose of cobalt-60 to obtain the finished product; The hydrogel dressing has a dual-network structure, which is constructed by a process of first blending and then uniformly ion-crosslinking an ionic crosslinking network and a physical entanglement network. The ionic crosslinking network is composed of sodium alginate and calcium ion crosslinking, and the physical entanglement network is formed by PVPK90 and sodium carboxymethyl cellulose through hydrogen bonds and chain entanglement. The berberine hydrochloride content in the Phellodendron amurense extract is ≥50% by weight, the purity of the Bletilla striata polysaccharide is ≥85% by weight and the molecular weight is 50-100kDa, and the glycoside content in the total glycosides of Centella asiatica is ≥80% by weight. The Bletilla striata polysaccharide serves as a healing-promoting component in the hydrogel dressing, promoting the transdermal absorption of the Phellodendron amurense extract and the total glycosides of Centella asiatica.
2. The preparation method according to claim 1, characterized in that, The sodium alginate has a molecular weight of 100-200 kDa, and a 1% aqueous solution has a viscosity of 200-400 mPa·s at 25°C. The degree of substitution of sodium carboxymethyl cellulose is 0.7-0.9; the molecular weight of PVPK90 is 1000-1500 kDa.
3. The preparation method according to claim 1, characterized in that, The Phellodendron bark extract was prepared by ethanol reflux extraction, the Bletilla striata polysaccharide was prepared by water extraction and alcohol precipitation, and the total glycosides of Centella asiatica were prepared by ethyl acetate extraction.
4. The preparation method according to claim 1, characterized in that, Step (3) must be carried out under light-protected conditions throughout. A brown stirring vessel or a light-shielding cloth can be used to avoid oxidative degradation of the Phellodendron bark extract and Centella asiatica total glycosides.
5. The application of the hydrogel dressing prepared by the method according to any one of claims 1 to 4 in the preparation of wound care products after fire needling, characterized in that, This dressing can be used for full-cycle care of fire needle wounds during the inflammatory phase (anti-inflammatory), the proliferative phase (promoting healing), and the remodeling phase (preventing scarring), achieving precise spatial distribution and dynamic controlled release of the drug over time.
Citation Information
Patent Citations
Composition for treating intractable skin infection, sores and ulcers and inflammation as well as preparation method and application of composition
CN121015679A
Three-dimensional network aqueous gel and manufacturing method thereof
US20230218800A1